Pertumbuhan Dan Hasil Tanaman Buncis Tegak (Phaseolus vulgaris L.) Akibat Pemberian Pupuk Kotoran Hewan Dan Beberapa Pupuk Organik Cair - Upik Nurmayulis; A. A. Fatmawaty; D Andini (Faculty of Agriculture, Pattimura University, 2014)
The purpose of this research was to find out the interaction effect between animal manure and some organic liquid on growth and yield of kidney beans. The research was conducted from May to July 2013 in Kampung Kopi, Desa Sukalaba, Kecamatan Gunungsari, Serang, Banten. The experiment was set up in Factorial Completely Randomized Block Design with three replicates to test three kinds of cattle manure i.e. cow manure, chicken manure and goat manure; and four kind of organic liquid fertilizers i.e M-Bio, Extragen, Terobos and Poc Nasa. The result of this research demonstrated that there was no interaction effect between the two treatment factors on all of growth and yield parameters measured. Neither manure nor liquid fertilizer also had no effect on growt and yield of kidney bean.